Effect of peri-operative infusion of dexmedetomidine in pre-eclamptic pregnant women undergoing elective caesarian section under general anesthesia - Amr M.A. Abdelmalk; Osama H. Ahmed; Medhat H. Allam (Al-Azhar Assiut Medical Journal)
Background and aim Dexmedetomidine has (DEX) been effectively used as an additional treatment to improve inadequate pain relief provided by systemic opioids in laboring patients. This study aimed to investigate the effect of infusion of DEX in the perioperative period in mild pre-eclamptic women planned for cesarean section on general anesthesia. Patients and methods This prospective double-blind randomized study was conducted on 90 pregnant women of American Society of Anesthesiologists physical status II or III, aged 21–40 years proved to have mild preeclampsia, planned for cesarean section on general anesthesia in a period from May 2021 to November 2023. The patients were randomly assigned into two equal groups, each comprising 45 patients. Results Heart rate readings at 15 min postinfusion and after induction were notably lower in the DEX group (D) in comparison to the control group (C). Both Systolic and diastolic blood pressure at 15 min after infusion, following induction, and then every 2 h through 6 h postoperatively were reduced in group D relative to group C. The visual analogue scalescores at 2-, 4-, and 6 h postsurgery were significantly lower in the DEX group compared with the control group. Finally, the Ramsay Sedation Scale score immediately after surgery was significantly increased in group D than in group C. Conclusion This study showed that giving DEX at a dosage of 0.5 mic/kg/h to pre-eclamptic patients having elective cesarean sections in group C. effectively helps stabilize maternal hemodynamic indicators while having minimal impact on the fetus.